Revisiting the Haloarcula marismortui 50S ribosomal subunit model. (21st May 2013) - Gabdulkhakov, Azat; Nikonov, Stanislav; Garber, Maria
<x xml:space="preserve">Abstract</x> The structure of the large ribosomal subunit from the halophilic archaeon Haloarcula marismortui (Hma) is the only crystal structure of an archaeal ribosomal particle that has been determined to date. However, the first model of the Hma 50S ribosomal subunit contained some gaps: the structures of functionally important mobile lateral protuberances were not visualized. Subsequently, some parts of the P (L12) stalk base were visualized at 3.0 Å resolution [Kavran & Steitz (2007), J. Mol. Biol.371, 1047–1059]: the RNA‐binding domain of r‐protein P0 (L10), the C‐terminal domain of L11 and helices 43 and 44 of the 23 S rRNA. Here, the 2.4 Å resolution electron‐density map of the Hma 50S ribosomal subunit was revisited and approximately two‐thirds of the P0 protein, residues 1–58 of the N‐terminal domains of two P1 protein molecules, residues 130–156 of L11, the full‐length r‐protein LX, nucleotides 2137–2149 and 2226–2237 of the 23S rRNA helix H76 forming the L1 stalk, nucleotides 2339–2343 of the 23S rRNA (contacting L5 protein) and loops 29–34 and 108–128 of protein L5 could be visualized. Thus, this paper provides a supplemented version of the Hma 50S ribosomal subunit model.